PEDAGOGICAL STRATEGIES FOR DEVELOPING ADOLESCENTS' COMMUNICATIVE COMPETENCE THROUGH FAMILY-SCHOOL COOPERATION - Evatov Saminjon Sobirovich (International Journal of Literature and Language Studies, 2026)
Abstract. This article analyses the pedagogical potential of family-school cooperation and effective strategies for developing adolescents' communicative competence. It discusses the psychological and pedagogical characteristics of adolescence, the components of communicative competence, and the mechanisms for its development. It also highlights the importance of collaborative learning, reflective activity, interactive methods, family communication technologies, and digital communication tools. The findings show that close cooperation between the family and the school is an important pedagogical factor in developing adolescents' communicative competence.